(untitled) (Revista Lusófona de Educação, 2026)
Global Citizenship Education and People on the Move: Proposals for Latin America (Part One) The first global trend is the theoretical and narrative tension between definitions of what constitutes economic development and growth in the context of environmental protections, what is the nature of democracy and its governance, and what is the role of education in this “new” modernity of capitalism (Hartmut, 2013). As stated in a research project: “The reality is that we are on the edge of a planetary cliff, and humanity has two options to choose from. On the one hand, it is the continued expansion of democracy, a further extension of human rights and freedoms, and concrete efforts to address the growing threats and realities of climate change. On the other hand, the dismantling of democracy to be replaced by a populist and authoritarian government, the increase in attacks against marginalized, oppressed, and exploited populations in the world, and the acceleration of the degradation of planet Earth.